Financial Feasibility Analysis By Utilizing Float Time On Profitability In High-Rise Building Construction Projects - Mahardini, Hirdayanti Andina Raissha; Putra, I Nyoman Dita Pahang (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Construction projects face time risks, such as delays causing cost overruns, and cost risks, including cash flow bottlenecks hindering funding. Effective cash flow management is critical to ensure project profitability and success, measured through both physical and financial aspects. This study compares the optimal profits of projects without a down payment and with a 20% down payment, under float utilization rates of 0%, 25%, 50%, 75%, and 100%. Using Microsoft Project 2021 and the Precedence Diagram Method (PDM), critical path and float durations were analyzed to assess financial feasibility with Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Return on Investment (ROI). Results show the most optimal cash flow without a down payment occurs at 50% float utilization, yielding an NPV of IDR 2,121,722,719, a BCR of 1.0698, and an ROI of 6.98%. For a 20% down payment, optimal results occur at 25% float utilization, with an NPV of IDR 1,998,159,242, a BCR of 1.0568, and an ROI of 5.68%. These findings emphasize the importance of strategic cash flow planning to optimize financial performance in construction projects.